Consumption and productivity adjusted dependency ratio with household structure heterogeneity. - Han, Xuehui (Metro Manila, Philippines Asian Development Bank, 2017)
Population aging, now a new norm for almost all emerging economies, brings paramount challenges including increasing consumption burden from elderly people. A comprehensive policy reform, guided by a more scientific version of the dependency ratio, is needed to accommodate this new norm. This paper presents a new dependency ratio measure that takes into account the consumption needs of the young and elderly people, and the productivity of middle aged people. Using household survey data from Bangladesh, Cambodia, the Peoples Republic of China, Thailand, and VietNam, this paper estimates the factor of relative needs of people at different ages based on a regression model.
Keywords: Social rights -- Developing countries; Electronic books